How variable is Crepidotus variabilis? - Jančovičová, Soňa; Adamčíková, Katarína; Caboň, Miroslav; Adamčík, Slavomír (Phytotaxa, 2020)
This study evaluates the morphological concept of Crepidotus variabilis and similar taxa based on basidiospore and cheilocystidia characters. A phylogenetic analysis of the ITS region clearly distinguished C. variabilis var. variabilis from the two other distinct taxa of the same lineage, C. variabilis var. trichocystis and C. neotrichocystis. We also recognised one additional morphologically similar and undescribed species that belongs to the C. variabilis lineage. All four taxa can also be recognised morphologically using basidiospore and cheilocystidia characters. Our detailed statistical comparison of these characters improves the knowledge of their variability and specifies more precisely the morphological circumscription of the taxa within this group.